Makna Simbol “ZERO” Sebagai Pesan Non Verbal Yayasan Matahati Dalam Mencegah Penyebaran HIV Aids Di Kawasan Pangandaran - Ditha Prasanti; Hadi Suprapto Arifin; Ikhsan Fuady (Jurnal Komunikasi, 2020)
This article is the result of a study of health communication studies on HIV AIDS prevention and prevention by the Matahati Foundation in Pangandaran district. Like the iceberg phenomenon, the number of HIV AIDS in Pangandaran district is increasing, so that it attracts the attention of various parties, one of which is the Matahati Foundation. In this article, the method which used is qualitaitv method, in line with the aim of research that is describes the existence of a symbol used by the Matahati Foundation, namely the symbol "ZERO". If examined in communication studies, this ZERO symbol has a certain meaning in relation to the vision and mission of the Matahati Foundation itself. This was later revealed by the author in the discussion section of this article. The results showed that the symbol "ZERO" for the Matahati Foundation had several meanings, including: as a non-verbal message containing the meaning of the hopes of the Matahati Foundation in reducing the prevalence of HIV AIDS rates in Pangandaran district; the meaning of motivation for people with HIV AIDS to try to arrive at "ZERO" HIV AIDS, which means recovery; and the meaning of persuasion for the community to be together in order to achieve "ZERO" HIV AIDS in Pangandaran district. Artikel ini merupakan hasil penelitian kajian komunikasi kesehatan tentang pencegahan dan penanggulangan HIV AIDS yang dilakukan Yayasan Matahati di kabupaten Pangandaran. Layaknya fenomena gunung es, angka HIV AIDS di kabupaten Pangandaran semakin meningkat, sehingga menarik perhatian berbagai pihak, salah satunya adalah Yayasan Matahati. Dalam artikel ini, metode penelitian yang relevan digunakan adalah metode kualitatif, sebagaimana tujuan dari penelitian ini yaitu menggambarkan tentang adanya sebuah simbol yang digunakan oleh Yayasan Matahati, yaitu simbol “ZERO”. Jika diteliti dalam kajian komunikasi, simbol ZERO ini memiliki makna tertentu kaitannya dengan visi misi dari Yayasan Matahati sendiri. Hal tersebut yang kemudian diungkapkan penulis dalam bagian pembahasan artikel ini. Hasil penelitian menunjukkan bahwa simbol “ZERO” bagi Yayasan Matahati tersebut memiliki beberapa makna, di antaranya: sebagai pesan non verbal yang berisi makna harapan Yayasan Matahati dalam menurunkan prevalensi angka HIV AIDS di kabupaten Pangandaran; makna motivasi bagi para penyandang HIV AIDS agar berupaya untuk sampai pada “ZERO” HIV AIDS, yang berarti sembuh; dan makna persuasi bagi masyarakat untuk bersama-sama dalam rangka mencapai “ZERO” HIV AIDS di kabupaten Pangandaran.